The Effect of Paylater Features, Service Quality, and Free Shipping on Purchasing Decisions - Ningsih, Bella Sonia Tali Setya; Putri, Eskasari (Institut Bisnis dan Informatika Kesatuan, 2024)
The aim of this research is to determine the influence of paylater features, service quality, and free shipping on purchasing decisions on Shopee e-commerce. The method used in this research is a quantitative method. The population in this study are people who have purchased products using Shopee and used the paylater feature on Shopee. The sample obtained was 108 respondents. To select the sample size, this research used a purposive sampling technique, and individuals who were deemed to have data sources that met the research criteria were given a questionnaire. The measuring tool used is a closed questionnaire with 18 statements and distributed via Google Form. The technique used in this research is multiple linear regression analysis by carrying out validity tests, reliability tests, followed by hypothesis testing after the assumption tests are met. From the analysis carried out it can be concluded that: (1) The Paylater feature (X1) has a significant positive effect on purchasing decisions (Y). (2) Service Quality (X2) has a negative and insignificant effect on purchasing decisions (Y). (3) Free shipping (X3) has a significant positive effect on purchasing decisions (Y).